The dual impact of ictal and interictal burden in migraine: an analysis from the ObserVational survey of the Epidemiology, tReatment, and Care Of MigrainE (OVERCOME) Japan second study - Tsubasa Takizawa; Daisuke Danno; Ryotaro Ishii; Shiho Suzuki; Moemi Miura; Yoshinori Tanizawa; Satoshi Osaga; Michio Okada; Chie Hashimoto; Mika Komori (The Journal of Headache and Pain)
Abstract Background Migraine adversely affects many aspects of daily life. In addition to burdens during headaches (ictal period), burdens between headaches (interictal period) are increasingly recognized. In this analysis of the ObserVational survey of the Epidemiology, tReatment, and Care Of MigrainE in Japan (OVERCOME [Japan]) 2nd study, we evaluated the contribution of interictal burden to daily activities, quality of life, work, family, costs, and medical treatment. Methods The OVERCOME (Japan) 2nd study was a cross-sectional, web-based survey of 19,590 adults in Japan with migraine conducted between June and August 2023. Questionnaires included Headache Impact Test-6 (HIT-6), Migraine Interictal Burden Scale-4 (MIBS-4), Migraine Disability Assessment (MIDAS), Allodynia Symptom Checklist-12 (ASC-12), Migraine-Specific Quality-of-Life Questionnaire (MSQ), Impact of Migraine on Partners and Adolescent Children Scale (IMPAC), Work Productivity and Activity Impairment Questionnaire-Migraine (WPAI-M), and Migraine Treatment Optimization Questionnaire-6 (mTOQ-6). Additional questions asked about costs, frequency of migraine concerns between headaches, and experience with medical treatment. Analyses were conducted on subgroups based on HIT-6 and MIBS-4 scores: Severe (HIT-6 ≥ 60, MIBS-4 ≥ 3; n = 6854), High Interictal Burden (HIT-6 < 60, MIBS-4 ≥ 3; n = 2368), High Ictal Burden (HIT-6 ≥ 60, MIBS-4 < 3; n = 4253), and Milder (HIT-6 < 60, MIBS-4 < 3; n = 6115). Results Number of monthly headache days, total MIDAS score, and pain severity score were higher, and MSQ scores lower, in subgroups with higher HIT-6 (HIT-High) versus subgroups with lower HIT-6 (HIT-Low). Within both HIT-High and HIT-Low subgroups, those with higher MIBS-4 had higher MIDAS and lower MSQ. IMPAC grade, ASC-12 score, and WPAI-M absenteeism were higher in the High Interictal Burden subgroup versus the High Ictal Burden subgroup. Concerns between headaches were more frequent, and costs higher, in subgroups with higher MIBS-4 (MIBS-High) versus subgroups with lower MIBS-4 (MIBS-Low). Acute treatment prescription analgesics were more commonly used in HIT-High versus HIT-Low subgroups, but triptans, lasmiditan, and preventive drugs were more common in the High Interictal Burden subgroup versus the High Ictal Burden subgroup. Conclusions These results revealed that high interictal burden negatively affects multiple aspects of daily life in Japanese people with migraine independently of the impact of headaches. Graphical abstract